HUBUNGAN PENGETAHUAN TENTANG JAMBAN DENGAN PERILAKU PENGGUNAAN JAMBAN DI DESA TANJUNG GADAI KABUPATEN KEPULAUAN MERANTI - Lasiah Susanti; Martha Saptariza Y; Sonya Dewanti (Universitas Ahmad Dahlan, 2023)
Latrine utilisation is a form of sanitation to keep healthy environment. The problem is latrine utilisation affected by knowledge, behavior, education, attitude, and economy. According to Join Monitoring Program (JMP) WHO/UNICEF 2015, 51 milion indonesian people still defecate in random place. 12,9% Indonesian people did’t have appropriate latrine. Data from public health centre of Selat Panjang’s on 2018, there are 3 villages with low sanitation in Selat Panjang, Kepau Baru is the first villages with very low point, Teluk Buntal is the second and Tanjung Gadai is the third village. Where is health appropriate latrine is very rare, in contrast with 7 other villages in Selat Panjang. Located in Meranti archipelago, Selat Panjang consist of 10 remote villages that difficult to access and had their very own culture. Research conducting in Tanjung Gadai village because its more accessible than the other two villages, and the language is easy to understand. Research aim to know the relationship between knowledge of healthy latrines and latrines utilisation behavior in Tanjung Gadai village Meranti Island. This study used observational analytic study with a Cross Sectional approach. The research was conducted in the village of Tanjung Gadai, Meranti Islands Regency. The sampling technique used is Stratified Propotionate Random Sampling and tested statistically using the Correlation Test Spearman. The research result showed that there is significant relationship between the respondents’ knowledge and their behaviour in using toilet at Tanjung Gadai village, regency of Meranti Archipelago 0,017. ρ <0.05, Hence, there is significant relationship between the knowledge about t healthy latrines and latrines utilisation behavior in Tanjung Gadai village, Meranti Archipelago Regency.